Student Personality Development Efforts through Individual Counseling Services - Zahra Pebrianti, Ajeung; Sharini, Iip; Fikriyah (Annpublisher, 2024)
This paper results from our research to determine the efforts to develop student personality through individual counseling services at SD Negeri 1 Watubelah. The results of the interviews show that individual counseling refers to the results of student understanding because students have different problems. The strategies applied by class teachers in individual counseling efforts by observing their students and building good relations with their students, distributing questionnaires to find out their students' problems, the competence of class teachers must be increased so that the implementation of individual counseling guidance in elementary schools is well programmed.